“Determinación de hierro, hemoglobina y hematocrito como aporte para el establecimiento de valores de referencia en estudiantes de unidades educativas rurales del Cantón Riobamba” - Canseco Villota, Nataly del Roció (2018)
The present work has the purpose of helping the contribution of reference values of iron, hemoglobin and hematocrit of the canton Riobamba, since there are no values that help to know the real state of health with a better interpretation. For which the following scheme was developed. Numeral 1 and its respective sections is made up of: The Problem Statement in which the importance of carrying out the study to give a contribution with the reference values is described, in addition the Justification and the Objectives are included. Numeral 2 and its respective sections is made up of: The Theoretical Foundation (state of the art), themes that were used in the development of research. Numeral 3 and its respective sections is made up of: The Applied Methodology in research, Population and Sample, Techniques as a survey, methodology that contributes to the investigative process. Numeral 4 and its respective sections are made up of, the analysis and discussion of results. Numeral 5 and its respective sections is made up of: The Conclusions and Recommendations of the investigation.